Natural variability in yield and properties of Balanites aegyptiaca (L.) Delile kernel oil from different locations in Nigeria - Lucky Dartsa Wakawa; Adejoke Olukemi Akinyele (BIORE Scientia Publisher, 2024)
Balanites aegyptiaca known as the desert date is an underutilized and neglected wild fruit tree/shrub of the arid and semi-arid zones with high economic potential. This study, therefore, was conducted to investigate the yield, physico-chemical and phytochemical properties, proximate and mineral composition of desert date kernel oil from different locations. Oil was extracted using the soxhlet apparatus, while hexane served as solvent. Standard procedures were used to determine the yield and properties of desert date kernel oil. The data obtained were subjected to the analysis of variance (p< 0.05). Oil yield (%) was found to range from 21.09±1.04-43.95±1.85 and varied significantly among the locations. Acid and saponification values (mg KOH/g) increased significantly from 2.11±0.07 to 1.36±0.07 and 76.35±0.22 to 179.85±0.90, respectively. The refractive index ranged from 1.36±0.15 to 1.48±0.06, while the iodine value (mg KOH/g) varied significantly from 67.07±1.53 to 85.33±2.52. Saponins, tannins, and phenol were discovered to vary significantly among the locations, and range from 3.82±0.30 -5.83±0.45 (mg/100 g), 1.31±0.10 - 1.68±0.03 (mg/100 g) and 1.51±0.05 - 2.09±0.06 (mg/100 g), respectively. The broad variability observed in the properties of desert date kernel oil among locations indicates the feasibility of improving kernel oil yield and properties through selection